2017
DOI: 10.1016/j.annemergmed.2017.07.266
|View full text |Cite
|
Sign up to set email alerts
|

288 Emergency Department-Based Palliative Interventions

Abstract: Study Objectives: Our objective was to develop a set of physical exam and laboratory findings that in selected pediatric patients, combined with the FAST exam results, were sensitive and specific in detecting intra-abdominal injuries that correlated with CT scan results.Methods: This was a retrospective chart review of all trauma patients aged 0-17 years who were evaluated at an academic American College of Surgeons (ACS) verified Level 1 Adult and Pediatric Trauma center between January 1, 2015 and December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Patients with unmet PC needs who received a PC consultation postdischarge was reported to be 5%, 28 6%, 31 11%, 37,38 and 29% 12 in five studies. Five studies 23,25,26,36,46 applied an intervention with the objective of promoting PC consultations and reported that a range between 32% and 47% of patients with unmet PC needs received a PC consultation in the ED or hospital 23,25,26,46 . One of the intervention studies reported that 90% of patients with unmet PC needs received a referral to PC post‐discharge; however, only 43% of the patients attended the PC consultation 36 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with unmet PC needs who received a PC consultation postdischarge was reported to be 5%, 28 6%, 31 11%, 37,38 and 29% 12 in five studies. Five studies 23,25,26,36,46 applied an intervention with the objective of promoting PC consultations and reported that a range between 32% and 47% of patients with unmet PC needs received a PC consultation in the ED or hospital 23,25,26,46 . One of the intervention studies reported that 90% of patients with unmet PC needs received a referral to PC post‐discharge; however, only 43% of the patients attended the PC consultation 36 …”
Section: Resultsmentioning
confidence: 99%
“…Unlike many of the other screening tools, the original SPEED tool does not have prespecified criteria for a patient to be considered to have “unmet PC needs,” but, rather, aims to assist physicians identify specific needs of the patient. Two studies utilized a modified five‐item version of the SPEED instrument, which includes five questions regarding difficulties in pain management, home care, medication management, psychological support, and goals of care 23,46 . The items of the five‐item SPEED tool are scored on a Likert scale, however, the threshold score for each domain to identify a patient with unmet PC needs was not reported 23,46 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations